Reconsidering the Electoral Connection of Speeches: The Impact of Electoral Vulnerability on Legislative Speechmaking in a Preferential Voting System. Issue 4 (27th September 2020) - Poyet, Corentin; Raunio, Tapio
Abstract : Recent literature highlights the incentives emanating from the electoral system and intraparty politics to explain unequal access to the plenary floor. This article contributes to the literature by investigating the effect of electoral vulnerability on the likelihood to deliver speeches in a preferential voting system. Drawing on data from Finland, it argues that intraparty vulnerability has a negative impact on the likelihood to deliver speeches, whereas the opposite effect is expected regarding interparty vulnerability. The findings show that intraparty vulnerability is negatively correlated with the number of speeches and that this effect is even larger when intraparty competition is tougher. The article underlines the importance of individual electoral goals when exploring legislative speechmaking. It also shows the need to distinguish the two forms of vulnerability and to consider factors that mediate the electoral connection.